Language assistants' views on the training provided by bilingual programs in Madrid - Buckingham, Lyndsay R. (Pulso. Revista de educación, 2018)
This study explores the effectiveness of language assistant (LA) training in Madrid’s bilingual programs. LAs rated their preparedness and enthusiasm at the beginning of the academic year, and reported on their training and its applicability to future tasks. It was found that LAs perceived deficiencies in their training despite feelings of enthusiasm and usefulness when taking on responsibilities. LAs reported discrepancies between their training and their duties which resulted in them feeling ill-prepared. Therefore, it is recommended that bilingual programs examine the role of the LA and create a comprehensive training plan that efficiently prepares the diverse body of LAs.
Keywords: Auxiliar de conversación; Colegios bilingües; Rol; Percepción; Formación